Protecting against brain damage by improving treatment in neonates with hypoglycaemia: ProBrain-D—a study protocol of a prospective longitudinal study. Issue 8 (19th August 2022) - Hoermann, Henrike; Roeper, Marcia; Dafsari, Roschan Salimi; Koestner, Felix; Schneble, Dominik; von Zezschwitz, Dunja; Mayatepek, Ertan; Kummer, Sebastian; Meissner, Thomas
Abstract : Introduction: Although neonatal hypoglycaemia is the most common metabolic problem in neonates, there is no standard guideline for screening. Additionally, treatment of neonatal hypoglycaemia and glucose administration thresholds are discussed controversially. Severe hypoglycaemia can lead to brain damage, but data on the effects of mild hypoglycaemia on neurological development are limited. To our knowledge, this is the first prospective longitudinal cohort study to analyse if the implementation of a new diagnosis and treatment standard for neonatal hypoglycaemia may improve the outcome of neonates at risk for hypoglycaemia, especially concerning neurodevelopment. Furthermore, the acceptance and feasibility of the standard among different professional groups and parents are analysed. Methods and analysis: After implementation of a structured standard operating procedure (SOP), detailing preventive measures, blood glucose screening and neonatal hypoglycaemia treatment in a tertiary care hospital, 678 neonates ≥35+0 weeks of gestation will be recruited in a monocentric prospective cohort study. For comparison, 139 children born before the implementation of this new SOP, who had risk factors for neonatal hypoglycaemia or qualified for blood glucose measurements are recruited (retrospective cohort). For the primary end point, comparative analyses between and within the prospective and retrospective cohorts will be performed regarding the neurological outcome at 2–2.5 years of age in Bayley Scales of Infant Development. Furthermore, comprehensive clinical data and data on nutrition and developmental milestones are assessed at different time points (6 weeks, 6, 12, 18 and 24 months) in the prospective cohort. Acceptance and feasibility of the new standard are assessed using questionnaires. Ethics and dissemination: The study has been approved by the Ethics Committee of the Medical Faculty of the Heinrich-Heine-University Düsseldorf (20201162). The results of this study will be disseminated through peer-reviewed journals and presented at international conferences. Trial registration number: DRKS00024086.